2012
DOI: 10.4049/jimmunol.1102281
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Combined with TGF-β Converts Human Invariant NKT Cells into Suppressive Foxp3+ Regulatory Cells

Abstract: Invariant NKT (iNKT) cells constitute a versatile T cell subset with important regulatory functions, which are thought to result essentially from their capacity to promptly produce cytokines that influence the Th1/Th2 balance. In this study, we report that these cells can also express Foxp3, an important transcriptional regulator associated with suppressive activity, once they have been exposed to TGF-β. Foxp3 was expressed by iNKT cells from both peripheral and cord blood. CD4+ iNKT cells acquired Foxp3 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
54
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 53 publications
3
54
1
Order By: Relevance
“…In this study, we show that both IL-10 and rapamycin promote FOXP3 expression in iNKT cell lines, whereas in contrast to previous reports using ex vivo cells (4)(5)(6), stimulation of these lines in the presence of TGF-b did not result in increased levels of FOXP3 in iNKT cells. Complementing recent data (6), we show that a suppressive phenotype was only induced when iNKT cell lines were cultured in the presence of rapamycin, irrespective of the additional presence of IL-10 or TGF-b.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In this study, we show that both IL-10 and rapamycin promote FOXP3 expression in iNKT cell lines, whereas in contrast to previous reports using ex vivo cells (4)(5)(6), stimulation of these lines in the presence of TGF-b did not result in increased levels of FOXP3 in iNKT cells. Complementing recent data (6), we show that a suppressive phenotype was only induced when iNKT cell lines were cultured in the presence of rapamycin, irrespective of the additional presence of IL-10 or TGF-b.…”
Section: Discussioncontrasting
confidence: 99%
“…We showed that FOXP3 could be induced in iNKT cells upon culture with IL-10 and rapamycin but not upon culture with TGF-b as previously described (6). There are several reasons that may account for this observed discrepancy.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations